Trade Finance during the 2008–9 Trade Collapse : Key Takeaways - Chauffour, Jean-Pierre (World Bank, Washington, DC, 2012)
Trade finance matters for trade, and when financial markets and world trade collapsed three years ago, a shortage in trade finance was hailed as a possible culprit. Because of the potential for global repercussions, world leaders called on the international community to act swiftly to avoid a depression. Governments and international institutions intervened to mitigate the impacts of the crisis. Then the economy bounced back, and trade picked up. But what did we learn from the crisis? In retrospect, what role did trade finance actually play? Did the freeze in the financial markets cause the unprecedented drop in global trade in 2008-9? This note presents evidence on the role of trade finance during 2008-9 and highlights a few takeaways on the data and knowledge gap of trade finance and government interventions during financial crises.